Five-element high-entropy sulfide nanoflower catalytic material and preparation method and application thereof
Patent Information
- Application Number
- CN202611298117.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]本发明所要解决的技术问题是:现有单金属硫化物催化剂存在活性位点类型单一、电子结构调控能力有限的问题,而现有高熵硫化物材料的制备方法相对有限,部分材料存在形貌不可控、活性位点暴露不足以及反应物传输效率较低的问题
[0017]本发明与现有技术相比,具有以下有益效果(1)通过构建由Bi、In、Sn、Sb和M五种金属元素组成的五元高熵硫化物体系,利用五种金属元素之间的协同作用调节材料电子结构,优化了二氧化碳还原过程中关键中间体的吸附行为。五种金属元素以等摩尔比例在阳离子位点上均匀分布,构型熵≥12.47 J/(mol·K),材料具有与Bi2S3相对应的单一固溶体相,提高了电催化二氧化碳还原制甲酸的选择性和催化活性。(2)通过水热条件下原位反应自组装形成三维纳米花结构,纳米花由二维纳米片组装形成,无需额外添加模板剂或结构导向剂。纳米花结构具有较大的比表面积和丰富的边缘活性位点,开放的三维传质通道有利于提高电解液渗透能力和反应物扩散效率,进一步提升了催化反应速率。(3)通过简单水热合成方法制备五元高熵硫化物纳米花材料,反应条件温和,操作步骤简便,无需高温煅烧或复杂后处理,易于规模化生产。该制备方法具有普适性,通过替换第五种金属盐即可制备不同组成的五元高熵硫化物纳米花材料,所得产物均保持单一固溶体相和纳米花形貌,适用于多种催化应用场景。(4)通过将五元高熵硫化物纳米花催化材料负载于导电基底上制备工作电极,在含有二氧化碳的电解液中进行电催化还原反应,在宽电位范围内甲酸的法拉第效率可达到80%以上,12小时稳定性测试中性能无明显衰减,具有良好的催化活性和结构稳定性。
Smart Images

Figure CN122879738A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrocatalytic materials technology, specifically to a five-element high-entropy sulfide nanoflower catalytic material, its preparation method, and its application. Background Technology
[0002] With the rapid development of industrialization, the massive consumption of fossil fuels has led to a continuous increase in carbon dioxide emissions, triggering global climate change and energy and environmental problems. Developing efficient carbon dioxide resource utilization technologies to convert carbon dioxide into high-value-added chemicals is of great significance for achieving carbon cycle and sustainable energy development. Electrocatalytic carbon dioxide reduction reactions can utilize renewable electricity to drive the conversion of carbon dioxide into high-value chemicals such as carbon monoxide, formic acid, methanol, and hydrocarbons, representing an important technological approach for carbon dioxide resource utilization. Formic acid, as an important chemical raw material and liquid hydrogen storage carrier, has high economic value; therefore, the development of highly selective and stable formic acid generation catalysts has attracted widespread attention. Currently, p-block metal-based materials such as bismuth, tin, and antimony show great application potential in the electrocatalytic reduction of carbon dioxide to formic acid due to their good carbon dioxide adsorption capacity and suitable adsorption capacity for oxygen-containing intermediates. However, traditional single-metal sulfide catalysts typically suffer from problems such as a single type of active site, limited electronic structure regulation capability, and difficulty in further improving catalytic performance. Furthermore, some metal sulfide materials are prone to structural changes during long-term electrocatalysis, leading to a decrease in catalytic activity and stability. In recent years, high-entropy materials have attracted widespread attention in the field of catalysis due to their multi-principal-element composition, lattice distortion, and unique electronic structure modulation capabilities. By introducing multiple metal elements to form high-entropy structures, the synergistic effect between different elements can be used to regulate the electronic state of the material surface, optimize the adsorption behavior of reaction intermediates, and thus improve catalytic reaction performance. However, the preparation methods of high-entropy sulfide materials are still relatively limited, and some materials suffer from problems such as uncontrollable morphology, insufficient exposure of active sites, and low reactant transport efficiency. On the other hand, nanoflower structures are usually assembled from two-dimensional nanosheet units, possessing a large specific surface area, abundant edge active sites, and open three-dimensional mass transfer channels, which are beneficial for improving electrolyte penetration and reactant diffusion efficiency. Therefore, constructing high-entropy sulfide materials with special morphological structures is expected to further improve the electrocatalytic carbon dioxide reduction performance.
[0003] Therefore, developing a pentagonal high-entropy sulfide nanoflower material with a simple preparation method, controllable structure, and high catalytic performance is of great significance for improving the electrocatalytic reduction of carbon dioxide to formic acid. Summary of the Invention
[0004] The technical problem to be solved by the present invention is that existing single metal sulfide catalysts have the problems of limited active site types and limited electronic structure control capabilities, while the preparation methods of existing high entropy sulfide materials are relatively limited, and some materials have problems such as uncontrollable morphology, insufficient exposure of active sites and low reactant transport efficiency.
[0005] To address the aforementioned technical problems, this invention provides a method for preparing a pentagonal high-entropy sulfide nanoflower catalytic material, comprising the following steps: Step S100: Add the metal salts of the five metal elements and the sulfur-containing ligands to the solvent and mix them evenly to obtain a precursor solution. The five metal elements include Bi, In, Sn, Sb and M, where M is selected from one of Cr, Cu, Zn, Ga, La, Cd, Sc, Co, Ni and Pb. No template agent or structure directing agent is added in step S100. Step S200: The precursor solution obtained in step S100 is subjected to a hydrothermal reaction to obtain a five-element high-entropy sulfide material; Step S300: The product obtained in step S200 is centrifuged, washed and dried sequentially to obtain a pentagonal high-entropy sulfide nanoflower catalytic material.
[0006] Furthermore, step S100 further includes: Step S110: Add the metal salts of the five metal elements and the sulfur-containing ligands to the solvent, with the molar ratio of the five metal elements being 1:1:1:1:1; Step S120: Stir to fully dissolve the metal salt and sulfur-containing ligands, and mix evenly to obtain a precursor solution.
[0007] Further, in step S110, the metal salt includes at least one of chloride, nitrate, acetate, and sulfate; the sulfur-containing ligand includes at least one of L-cysteine, thiourea, thioacetamide, thiol, diphenyl disulfide, dimethyl sulfoxide, and polysulfide organic amine; and the solvent includes at least one of ethylene glycol and ethanol.
[0008] Furthermore, in step S110, the sulfur-containing ligand is L-cysteine, and the solvent is ethylene glycol; the molar amount of the sulfur-containing ligand is twice the total molar amount of the five metal salts.
[0009] Furthermore, step S200 further includes: Step S210: Transfer the precursor solution obtained in step S120 to a hydrothermal reactor; Step S220: The hydrothermal reactor is subjected to a hydrothermal reaction at a temperature of 120℃ to 200℃ for 12 to 36 hours. The hydrothermal reaction conditions are controlled to allow the five metal elements to react in situ with sulfur-containing ligands and self-assemble into a three-dimensional nanoflower structure composed of two-dimensional nanosheets. The product forms a single solid solution crystal structure corresponding to Bi2S3. The five metal elements Bi, In, Sn, Sb and M are uniformly distributed at the cation sites, and the configuration entropy is ≥12.47 J / (mol·K).
[0010] Furthermore, in step S220, the hydrothermal reaction temperature is 160°C and the reaction time is 24 hours.
[0011] Furthermore, step S300 further includes: Step S310: The product obtained in step S220 is centrifuged and washed sequentially with deionized water and anhydrous ethanol; Step S320: The washed product is vacuum dried at a temperature of 50°C to 80°C to obtain a pentagonal high-entropy sulfide nanoflower catalytic material.
[0012] Furthermore, in step S320, the drying temperature is 60°C.
[0013] This invention also provides a pentagonal high-entropy sulfide nanoflower catalytic material, prepared by the above-described method, with the general chemical formula BiInSnSbMSx, wherein M is selected from one of Cr, Cu, Zn, Ga, La, Cd, Sc, Co, Ni, and Pb; the material has a three-dimensional nanoflower structure formed by the self-assembly of two-dimensional nanosheets; the material has a single solid solution crystal structure corresponding to Bi2S3; the five metal elements Bi, In, Sn, Sb, and M are uniformly distributed at the cation sites, with a configuration entropy ≥ 12.47 J / (mol·K).
[0014] Furthermore, the diameter of the three-dimensional nanoflower structure is from hundreds of nanometers to several micrometers, and the thickness of the two-dimensional nanosheet is from several nanometers to tens of nanometers; the various metal elements and sulfur elements are uniformly distributed in the nanoflower structure.
[0015] The present invention also provides the application of the above-mentioned pentagonal high-entropy sulfide nanoflower catalytic material in electrocatalytic carbon dioxide reduction. The pentagonal high-entropy sulfide nanoflower catalytic material is loaded onto a conductive substrate to prepare a working electrode, and the electrocatalytic carbon dioxide reduction reaction is carried out in an electrolyte containing carbon dioxide.
[0016] Furthermore, the products of the electrocatalytic carbon dioxide reduction reaction include at least one of carbon monoxide, formic acid, methanol, and hydrocarbons, with formic acid being the main product. The faradaic efficiency of formic acid can reach over 80% over a wide potential range, and the faradaic efficiency of formic acid shows no significant decay in the 12-hour stability test.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) By constructing a pentagonal high-entropy sulfide system composed of five metal elements Bi, In, Sn, Sb and M, the synergistic effect between the five metal elements is used to regulate the electronic structure of the material and optimize the adsorption behavior of key intermediates in the carbon dioxide reduction process. The five metal elements are uniformly distributed on the cation sites in an equimolar ratio, with a configuration entropy ≥12.47 J / (mol·K). The material has a single solid solution phase corresponding to Bi2S3, which improves the selectivity and catalytic activity of electrocatalytic carbon dioxide reduction to formic acid. (2) A three-dimensional nanoflower structure is formed by in-situ reaction self-assembly under hydrothermal conditions. The nanoflower is assembled from two-dimensional nanosheets without the need for additional template agents or structure directing agents. The nanoflower structure has a large specific surface area and abundant edge active sites. The open three-dimensional mass transfer channels are conducive to improving the electrolyte penetration capacity and reactant diffusion efficiency, further enhancing the catalytic reaction rate. (3) Five-membered high-entropy sulfide nanoflower materials were prepared by a simple hydrothermal synthesis method. The reaction conditions were mild, the operation steps were simple, and no high-temperature calcination or complex post-treatment was required, making it easy to scale up production. This preparation method is universal. By replacing the fifth metal salt, five-membered high-entropy sulfide nanoflower materials with different compositions can be prepared. The products obtained all maintain a single solid solution phase and nanoflower morphology, which is suitable for a variety of catalytic applications. (4) By loading the five-membered high-entropy sulfide nanoflower catalytic material onto a conductive substrate to prepare a working electrode, an electrocatalytic reduction reaction was carried out in an electrolyte containing carbon dioxide. The Faradaic efficiency of formic acid can reach more than 80% over a wide potential range. The performance showed no significant decay in the 12-hour stability test, indicating good catalytic activity and structural stability.
[0018] The present invention will now be further described with reference to the accompanying drawings. Attached Figure Description
[0019] Figure 1 The image shows the X-ray diffraction pattern of the pentagonal high-entropy sulfide nanoflower material prepared in Example 1.
[0020] Figure 2 The images are transmission electron microscope images of pentagonal high-entropy sulfide nanoflower materials, where (a) is BiInSnSbZnSx nanoflower material and (b) is BiInSnSbCuSx nanoflower material.
[0021] Figure 3 The elemental distribution diagram of BiInSnSbZnSx nanoflower materials.
[0022] Figure 4 The elemental distribution diagram of BiInSnSbCuSx nanoflower materials.
[0023] Figure 5The Faraday efficiency curves for the electrocatalytic carbon dioxide reduction products of BiInSnSbZnSx nanoflower materials are shown.
[0024] Figure 6 The curves show partial current density of the electrocatalytic carbon dioxide reduction products of BiInSnSbZnSx nanoflower materials.
[0025] Figure 7 The 12-hour stability test curve of BiInSnSbZnSx nanoflower material for electrocatalytic carbon dioxide reduction.
[0026] Figure 8 Linear sweep voltammetry curves for the electrocatalytic reduction of carbon dioxide by BiInSnSbZnSx nanoflower materials. Detailed Implementation
[0027] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0028] This invention provides a method for preparing a pentagonal high-entropy sulfide nanoflower catalytic material, comprising the following steps: Step S100: Prepare the precursor solution. Step S100 further includes: Step S110: Add the metal salts of five metallic elements and sulfur-containing ligands to the solvent. The five metallic elements include Bi, In, Sn, Sb, and M, where M is selected from Cr, Cu, Zn, Ga, La, Cd, Sc, Co, Ni, and Pb. The molar ratio of the five metallic elements is 1:1:1:1:1. The metal salts include at least one of chlorides, nitrates, acetates, and sulfates. The sulfur-containing ligands include at least one of L-cysteine, thiourea, thioacetamide, thiols, diphenyl disulfide, dimethyl sulfoxide, and polysulfide organic amines. The solvent includes at least one of ethylene glycol and ethanol.
[0029] Step S120: Stir to fully dissolve the metal salt and sulfur-containing ligands, and mix evenly to obtain a precursor solution.
[0030] Step S200: Perform a hydrothermal reaction. Step S200 further includes: Step S210: Transfer the precursor solution obtained in step S120 to a hydrothermal reactor.
[0031] Step S220: Place the hydrothermal reactor in an oven and carry out the hydrothermal reaction at a temperature of 120℃ to 200℃ for 12 to 36 hours. During the hydrothermal reaction, the metal elements and sulfur elements react in situ in the solvent and self-assemble to form a three-dimensional nanoflower structure composed of two-dimensional nanosheets. At the same time, the product forms a single solid solution crystal structure corresponding to Bi2S3. The five metal elements Bi, In, Sn, Sb, and M are uniformly distributed at the cation sites, and the configuration entropy is ≥12.47 J / (mol·K).
[0032] Step S300: Post-processing the product. Step S300 further includes: Step S310: The product obtained in step S220 is centrifuged and washed sequentially with deionized water and anhydrous ethanol.
[0033] Step S320: The washed product is vacuum dried at a temperature of 50°C to 80°C to obtain a pentagonal high-entropy sulfide nanoflower catalytic material.
[0034] The considerations for using steps S100 to S300 to prepare pentagonal high-entropy sulfide nanoflower catalytic materials are as follows: The hydrothermal method is simple to operate, with mild reaction conditions, and requires no high-temperature calcination or complex post-treatment steps. The metal salts of the five metal elements are uniformly mixed with sulfur-containing ligands in a solvent, and under hydrothermal conditions, they react in situ to generate sulfides and simultaneously self-assemble into nanoflower structures, without the need for template agents or structure-directing agents. The nanoflower structures are assembled from two-dimensional nanosheets, possessing a large specific surface area and abundant edge active sites, which is beneficial for improving electrolyte penetration and reactant diffusion efficiency. The introduction of the five metal elements in an equimolar ratio is conducive to the formation of a stable high-entropy solid solution structure, and the synergistic effect between different elements can regulate the electronic state of the material surface and optimize the adsorption behavior of reaction intermediates.
[0035] This invention also provides a pentagonal high-entropy sulfide nanoflower catalytic material prepared by the above method. This material is composed of five metal elements and sulfur, with the general chemical formula BiInSnSbMSx, where M is selected from Cr, Cu, Zn, Ga, La, Cd, Sc, Co, Ni, and Pb. The material has a crystal structure corresponding to Bi₂S₃, specifically a single solid solution crystal structure. The five metal elements are uniformly distributed at the cation sites, with a configuration entropy ≥ 12.47 J / (mol·K). The material possesses a three-dimensional nanoflower structure, formed by the self-assembly of two-dimensional nanosheets. The diameter of the nanoflower structure ranges from hundreds of nanometers to several micrometers, and the thickness of the two-dimensional nanosheets ranges from several nanometers to tens of nanometers. Each metal element and sulfur element are uniformly distributed within the nanoflower structure.
[0036] This invention also provides the application of the aforementioned pentagonal high-entropy sulfide nanoflower catalytic material in electrocatalytic carbon dioxide reduction. This application involves preparing a working electrode by loading the pentagonal high-entropy sulfide nanoflower catalytic material onto a conductive substrate, and then performing an electrocatalytic carbon dioxide reduction reaction in an electrolyte containing carbon dioxide. The products of the electrocatalytic carbon dioxide reduction reaction include at least one of carbon monoxide, formic acid, methanol, and hydrocarbons. Formic acid is the main product, and its Faradaic efficiency can reach over 80% over a wide potential range, with no significant decrease in Faradaic efficiency during a 12-hour stability test.
[0037] Example 1: Preparation of pentagonal high-entropy sulfide BiInSnSbZnSx nanoflower materials. Bismuth nitrate, indium nitrate, tin nitrate, antimony nitrate, and zinc nitrate were added to ethylene glycol in an equimolar ratio, with a total molar amount of 2 mmol for the five metal salts. L-cysteine was added as a sulfur-containing ligand, with a molar amount of L-cysteine twice the total molar amount of the metal salts. The mixture was stirred for 30 minutes to fully dissolve the metal salts and L-cysteine, obtaining a precursor solution. The precursor solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and subjected to a hydrothermal reaction at 160°C for 24 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The product was centrifuged and washed three times each with deionized water and anhydrous ethanol, and then vacuum-dried at 60°C for 12 hours to obtain a brownish-black powder, which is the BiInSnSbZnSx pentagonal high-entropy sulfide nanoflower catalytic material.
[0038] Reference Figure 1 X-ray diffraction patterns showed that the BiInSnSbZnSx material had a distinct crystalline phase, with diffraction peaks corresponding to the Bi2S3 phase and no impurity peaks, confirming that the material is a single solid solution phase. (Refer to...) Figure 2 (a) The transmission electron microscope image shows that the material has a distinct three-dimensional nanoflower morphology, which is formed by the assembly of two-dimensional nanosheets. (Refer to...) Figure 3 Transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDXPS) elemental surface scanning imaging revealed that Bi, In, Sn, Sb, Zn, and S elements were uniformly distributed within the nanoflower structure. Inductively coupled plasma atomic emission spectrometry (ICP-AES) analysis showed that the ratio of metallic elements in the material was Bi:In:Sn:Sb:Zn = 16.97:13.30:12.85:12.81:5.65, with a calculated configuration entropy of 13.3 J / (mol·K), which is higher than the high entropy threshold of 12.47 J / (mol·K), confirming its high entropy structural characteristics.
[0039] Example 2: Preparation of pentagonal high-entropy sulfide BiInSnSbCuSx nanoflower materials. Bismuth nitrate, indium nitrate, tin nitrate, antimony nitrate, and copper nitrate were added to ethylene glycol in an equimolar ratio, with a total molar amount of 2 mmol for the five metal salts. L-cysteine was added as a sulfur-containing ligand, with a molar amount of L-cysteine twice the total molar amount of the metal salts. The mixture was stirred for 30 minutes to fully dissolve the metal salts and L-cysteine, obtaining a precursor solution. The precursor solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and subjected to a hydrothermal reaction at 160°C for 24 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The product was centrifuged and washed three times each with deionized water and anhydrous ethanol, and then vacuum-dried at 60°C for 12 hours to obtain a brownish-black powder, which is the BiInSnSbCuSx pentagonal high-entropy sulfide nanoflower catalytic material.
[0040] Reference Figure 1 X-ray diffraction patterns showed that the BiInSnSbCuSx material exhibited Bi2S3 phase diffraction peaks consistent with BiInSnSbZnSx, confirming the universality of this method. (Refer to...) Figure 2 (b) Transmission electron microscopy images show that the material also exhibits a three-dimensional nanoflower morphology. (Refer to...) Figure 4 The elemental distribution diagram shows that Bi, In, Sn, Sb, Cu, and S are uniformly distributed in the nanoflower structure. Inductively coupled plasma atomic emission spectrometry (ICP-AES) analysis revealed that the ratio of metal elements in the material is Bi:In:Sn:Sb:Cu = 15.79:15.25:11.10:10.96:5.97, with a calculated configuration entropy of 13.2 J / (mol·K), which is higher than the high entropy threshold, confirming its high-entropy structural characteristics.
[0041] Example 3: Preparation of the BiInSnSbZnSx / CC electrode. Five milligrams of the BiInSnSbZnSx sample prepared in Example 1 were dispersed in a 500 μL mixed solution of water, ethanol, isopropanol, and perfluorosulfonic acid, with a volume ratio of 9:6:3:2. The sample was ultrasonically dispersed for 30 minutes to form a uniform suspension. The suspension was drop-coated onto a 1 cm × 1.5 cm sheet of carbon paper, resulting in a sample loading of 1 mg / cm² on the carbon paper electrode. After natural drying, the electrode for catalytic carbon dioxide reduction was obtained, denoted as BiInSnSbZnSx / CC.
[0042] Example 4: Electrochemical testing of the BiInSnSbZnSx / CC electrode. Electrocatalytic carbon dioxide reduction was tested using a flow electrolytic cell. The cathode electrolyte was a mixed aqueous solution of 0.05 mol / L sulfuric acid and 3 mol / L potassium chloride, and the anolyte was an aqueous solution of 0.05 mol / L sulfuric acid. The anode was a platinum sheet electrode, 1 cm × 1 cm in size, and the reference electrode was a silver / silver chloride electrode. Carbon dioxide gas was continuously introduced into the cathode electrolyte during the test. The distribution of catalytic carbon dioxide reduction products at different potentials was tested.
[0043] Reference Figure 5 The BiInSnSbZnSx / CC electrode exhibits a Faradaic efficiency exceeding 80% formic acid reduction over a wide potential range, demonstrating excellent selectivity for carbon dioxide reduction. (Reference) Figure 6 The partial current density of formic acid increases with increasing overpotential, indicating that the material possesses good catalytic activity. (Refer to...) Figure 7 In the 12-hour stability test, the Faraday efficiency of formic acid remained stable without significant decay, indicating that the material possesses excellent structural stability and catalytic durability. (Reference) Figure 8 Linear sweep voltammetry showed that the current density under a carbon dioxide atmosphere was significantly higher than that under an inert atmosphere, confirming that the material has significant catalytic activity for the carbon dioxide reduction reaction.
Claims
1. A method for preparing a pentagonal high-entropy sulfide nanoflower catalytic material, characterized in that, Includes the following steps: Step S100: Add the metal salts of the five metal elements and the sulfur-containing ligands to the solvent and mix them evenly to obtain a precursor solution. The five metal elements include Bi, In, Sn, Sb and M, wherein M is selected from one of Cr, Cu, Zn, Ga, La, Cd, Sc, Co, Ni and Pb, and no template agent or structure directing agent is added in step S100. Step S200: The precursor solution obtained in step S100 is subjected to a hydrothermal reaction to obtain a five-element high-entropy sulfide material. Step S300: The product obtained in step S200 is subjected to centrifugation, washing and drying to obtain a pentagonal high-entropy sulfide nanoflower catalytic material. Step S100 further includes: Step S110: Add the metal salts of the five metal elements and the sulfur-containing ligands to the solvent, with the molar ratio of the five metal elements being 1:1:1:1:1; Step S120: Stir to fully dissolve the metal salt and sulfur-containing ligand, and mix evenly to obtain a precursor solution; Step S200 further includes: Step S210: Transfer the precursor solution obtained in step S120 to a hydrothermal reactor; Step S220: The hydrothermal reactor is subjected to a hydrothermal reaction at a temperature of 120℃ to 200℃ for 12 to 36 hours. The hydrothermal reaction conditions are controlled so that the five metal elements react in situ with sulfur-containing ligands and self-assemble to form a three-dimensional nanoflower structure composed of two-dimensional nanosheets. The product forms a single solid solution crystal structure corresponding to Bi2S3. The five metal elements Bi, In, Sn, Sb and M are uniformly distributed at the cation sites, and the configuration entropy is ≥12.47 J / (mol·K). Step S300 further includes: Step S310: The product obtained in step S220 is centrifuged and washed sequentially with deionized water and anhydrous ethanol. Step S320: The washed product is vacuum dried at a temperature of 50°C to 80°C to obtain a pentagonal high-entropy sulfide nanoflower catalytic material.
2. The preparation method according to claim 1, characterized in that, In step S110, the metal salt includes at least one of chloride, nitrate, acetate, and sulfate. Sulfur-containing ligands include at least one of L-cysteine, thiourea, thioacetamide, thiols, diphenyl disulfide, dimethyl sulfoxide, and polysulfide organic amines; The solvent includes at least one of ethylene glycol and ethanol.
3. The preparation method according to claim 2, characterized in that, In step S110, the sulfur-containing ligand is L-cysteine, and the solvent is ethylene glycol; The molar amount of sulfur-containing ligands is twice the total molar amount of the five metal salts.
4. The preparation method according to claim 1, characterized in that, In step S220, the hydrothermal reaction temperature is 160℃ and the reaction time is 24 hours.
5. The preparation method according to claim 1, characterized in that, In step S320, the drying temperature is 60°C.
6. A pentagonal high-entropy sulfide nanoflower catalytic material, characterized in that, The general chemical formula is BiInSnSbMSx, where M is selected from one of Cr, Cu, Zn, Ga, La, Cd, Sc, Co, Ni, and Pb; The material has a three-dimensional nanoflower structure formed by the self-assembly of two-dimensional nanosheets; The material has a single solid solution crystal structure corresponding to Bi2S3; The five metallic elements Bi, In, Sn, Sb, and M are uniformly distributed at the cation sites, with a configuration entropy ≥ 12.47 J / (mol·K).
7. The pentagonal high-entropy sulfide nanoflower catalytic material according to claim 6, characterized in that, The diameter of the three-dimensional nanoflower structure ranges from hundreds of nanometers to several micrometers. The thickness of the two-dimensional nanosheets ranges from a few nanometers to tens of nanometers; the various metal elements and sulfur elements are uniformly distributed in the nanoflower structure.
8. The application of the pentagonal high-entropy sulfide nanoflower catalytic material according to claim 6 or 7 in electrocatalytic carbon dioxide reduction, characterized in that, The working electrode was prepared by loading the pentagonal high-entropy sulfide nanoflower catalytic material onto a conductive substrate, and then carried out an electrocatalytic carbon dioxide reduction reaction in an electrolyte containing carbon dioxide.